Analisis Kecerdasan Interpersonal Siswa Pada Mata Pelajaran IPAS di Sekolah Dasar - Hilman Mangkuwibawa; Salma Balqis; Siti Khozanatu Rohmah (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This research is motivated by the findings of student problems related to interpersonal intelligence. One of them is students who do not get acceptance and are bullied by their classmates. The purpose of this study was directed to describe the general description of students' interpersonal intelligence and the causal factors of the existence of student problems related to interpersonal intelligence. This research uses a descriptive method. The data collection techniques used were observation, questionnaires, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusions. The research was conducted in one of the elementary schools in the city of Bandung, class V students with a total of 32 people. The results showed that the general description of interpersonal intelligence of grade V students was in the moderate category and the causal factors of the existence of problems related to interpersonal intelligence, internal factors were influenced by the personality and self-awareness of students, external factors were influenced by relationships and parenting patterns applied by parents, family environment and surrounding communities, and social acceptance.